Analysis of mass distribution in dengue patients using bioelectrical impedance - Ibrahim, F.; Tiong, C.K.; Ismail, N.A.; Taib, M.N. (2005)
This paper describes the mass distribution in healthy subjects and dengue patients on the day of defervescence of fever using bioelectrical impedance analysis. A total of 223 healthy subjects (65 males and 158 females) and 210 dengue patients (119 males and 91 females) were studied. The ages for healthy subjects vary between 14 and 60 years old with mean age of 26.05 years while the ages for the dengue patients vary between 12 and 83 years old with mean age of 30.14 years. The parameters of mass distribution investigated were body cell mass (BCM) and extracellular mass (ECM). There were significant difference between healthy subjects and dengue patients for female in BCM and ECM beginning on fever day 0 till fever day 4 (p<0.001). There were also significant difference between healthy subjects and dengue patients for male in BCM for fever day 1 till fever day 3 and in ECM for all fever days (p<0.05). On the other hand, both the mean BCM and ECM for healthy and dengue groups for male were higher than female. Bioelectrical Impedance Analysis is a useful method to assess the changes of mass distribution in dengue patients. Â© 2005 IEEE.